Pelatihan Penegmbangan Desain We Pelatihan Pengembangan Desain Web Aplikasi Ujian Berbasis Komputer dengan Aplikasi Canva dan Figma - Sanjaya, M Rudi; Rosa Indah, Dwi; Wijaya Putra, Bayu; Afif, Hasnan; Arrijal Ismail, Ahmad; Riski, M. Rido; Trimaysella, Anne; Fatinah, Fitriasari; Izzatul Maula, Nurly; Merlin, Chalia; Liana Andini, Rahmah; Wulandari, Fitri (Jurnal SOLMA, 2024)
Background: Web-based applications have not been optimally utilized at the Miftahul Jannah Islamic Boarding School Foundation, Peninjauan Village, where teachers still have minimal knowledge in using technology for learning. Therefore, community service activities are needed to train them to use the Canva and Figma applications to design more modern and technology-based learning materials. The objectives of this Community Service are 1) Providing training on how to use the fiqma and canva applications so that they can use them effectively, 2) Improving the competence of participants in designing web-based designs with Figma and Canva application technology at the Miftahul Jannah Islamic Boarding School, Peninjauan Village, OKU Regency, South Sumatra Province. Method: This community service includes mentoring activities, discussions, questions and answers, demonstrations. The partner in this activity is the Miftahul Jannah Islamic Boarding School in Peninjauan Village, with 28 participants. The activity lasted for 3 days, with a duration of 8 hours each day. Results: Improving the competence of teachers at the Miftahul Jannah Islamic Boarding School in using the Canva and Figma applications to design computer-based exam web designs. Findings during the activity showed that, despite initial difficulties in adopting new technology, the training participants were able to adapt well after receiving clear guidance and opportunities for hands-on practice. Conclusion: The results of this activity were the creation of a computer-based exam web design for the Miftahul Jannah Islamic Boarding School in the review village to replace conventional exams with digital ones.